Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal display element, diamine, method for producing the same, and polymer
A novel liquid crystal aligning agent with a specific polymer structure improves solvent solubility and orientation, enhancing alignment properties and productivity in liquid crystal display elements.
Patent Information
- Application Number
- CN201980059567.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-14
- Filing Date
- 2019-09-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2039-09-12
Smart Images

Figure CN112703447B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a novel liquid crystal aligning agent and a liquid crystal aligning film, a liquid crystal display element, a novel diamine and a method for producing the same, and a polymer. Background Art
[0002] At present, liquid crystal display elements are widely used as display parts of personal computers, mobile phones, television receivers, etc. The liquid crystal display element has: for example, a liquid crystal layer sandwiched between an element substrate and a color filter substrate, a pixel electrode and a common electrode for applying an electric field to the liquid crystal layer, a liquid crystal orientation film for controlling the orientation of liquid crystal molecules in the liquid crystal layer, and a thin film transistor (TFT) for switching an electrical signal supplied to the pixel electrode. Among these, the liquid crystal orientation film is prepared by applying a polyimide-based liquid crystal orientation agent containing a polyamic acid (also called "polyamic acid") as a polyimide precursor and a solution of a polyimide as its imide product to a substrate and forming a film.
[0003] In recent years, the performance of liquid crystal display elements has been improved, the area has been increased, and the power saving of display devices has been promoted. In addition, they are used in various environments, and the properties required of liquid crystal alignment films have become stricter. Therefore, various methods such as changing the structure of polyamic acid and polyimide, mixing polyamic acid and polyimide with different properties, adding additives, etc., are used to improve the liquid crystal orientation, electrical properties, etc., and control the pretilt angle.
[0004] As an example of a method for improving the characteristics of a liquid crystal alignment film, a diamine having a novel structure as a raw material of a polyamic acid is proposed. For example, Patent Document 1 discloses a liquid crystal alignment agent containing a diamine having a novel structure and an aliphatic tetracarboxylic acid derivative, and by using the liquid crystal alignment agent, a liquid crystal display element having excellent voltage retention and reduced charge accumulation can be provided.
[0005] However, as the performance of liquid crystal display elements has been improved, the properties required for liquid crystal aligning films have also become stricter, and it has been difficult to satisfy all the required properties only with conventional techniques.
[0006] On the other hand, as a common method for orienting liquid crystals, a brushing method is used in which a polymer film such as polyimide is coated on a substrate such as glass, and the surface is rubbed in a predetermined direction with fibers such as nylon and polyester. However, the brushing method has the following concerns: the friction between the fibers and the polymer film causes fine dust to be generated and electrostatic discharge to occur, causing serious problems in the manufacture of liquid crystal panels.
[0007] Therefore, in order to solve the problems of the brushing method, it is known that there is a photo-orientation method that induces anisotropy by irradiating light for orienting the liquid crystal without rubbing the polymer film. For the photo-orientation method, by irradiating polarized ultraviolet rays, the polymer contained in the liquid crystal orientation film undergoes photo-decomposition reaction, photo-crosslinking reaction and other photo-reactions to fix the orientation direction of the liquid crystal. Such a photo-orientation method is being applied to liquid crystal display elements of the IPS method (In-Plane Switching) and FFS method (Fringe Field Switching) as a lateral electric field drive method in the high-precision and high-quality requirements of liquid crystal display elements (for example, refer to patent document 2). In addition, for the IPS method, in recent years, in order to further improve the orientation ability, a method combined with the PSA method is being developed.
[0008] However, the polyimide used in the photo-alignment method generally has poor solvent solubility, so it is difficult to directly apply the polyimide in the process of forming an alignment film by coating with a solution state of the polyimide. Therefore, after the precursors such as polyamic acid and polyamic acid ester with excellent solubility are coated and formed into polyimide through a heat treatment process, light irradiation is performed to orient it, but in order to irradiate the polyimide film with light to obtain sufficient liquid crystal orientation, more energy is required. Therefore, it is actually difficult to ensure productivity, and there is also a constraint that a heat treatment process is further required in order to obtain orientation stability after light irradiation.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: International Publication No. 2010 / 053128
[0012] Patent Document 2: Japanese Patent Application Publication No. 2013-080193 Summary of the invention
[0013] Problem that the invention aims to solve
[0014] The present invention has been made in view of such circumstances, and an object of the present invention is to provide a liquid crystal aligning agent, a liquid crystal aligning film, a liquid crystal display element, a diamine, a method for producing the same, and a polymer using a novel diamine for improving the characteristics of a liquid crystal display element.
[0015] Solutions for solving problems
[0016] The aspect of the present invention for solving the above-mentioned problems is a liquid crystal aligning agent containing at least one polymer selected from a polyimide precursor including a structural unit represented by the following formula [3-1] and a polyimide as an imide compound thereof.
[0017]
[0018] In formula [3-1], V 0 is a tetravalent organic group derived from a tetracarboxylic acid derivative, W 1 is a divalent organic group represented by the following formula [2-1], R 3 and R 4 Each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms.
[0019]
[0020] In formula [2-1], Y 1 is a tetravalent organic group having an alicyclic structure, X 1 , X 2 is a divalent organic group, Z 1 , Z 2 are each independently a single bond, -NH-, or -O-, R 1 and R 2 Each independently represents an alkyl group having 1 to 5 carbon atoms, and * represents a bonding site.
[0021] Effects of the Invention
[0022] According to the present invention, a novel liquid crystal aligning agent, a liquid crystal aligning film, and a liquid crystal display element, as well as a novel diamine and a method for producing the same, and a polymer for improving the characteristics of a liquid crystal display element can be provided. DETAILED DESCRIPTION
[0023] Hereinafter, the present invention will be described in more detail.
[0024] The liquid crystal aligning agent of the present invention contains at least one polymer (hereinafter also referred to as specific polymer A) selected from a polyimide precursor containing a structural unit represented by the following formula [3-1] and a polyimide as its imide compound. Specifically, it contains the specific polymer A and an organic solvent.
[0025]
[0026] Where V 0 is a tetravalent organic group derived from a tetracarboxylic acid derivative, W 1 is a divalent organic group represented by the following formula [2-1], R 3 and R 4 Each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms.
[0027]
[0028] Where Y 1is a tetravalent organic group having an alicyclic structure, X 1 , X 2 is a divalent organic group, Z 1 , Z 2 are each independently a single bond, -NH-, or -O-, R 1 and R 2 Each independently represents an alkyl group having 1 to 5 carbon atoms, and * represents a bonding site.
[0029] In the above, the structure of formula [2-1] is a divalent group derived from a diamine represented by the following formula [1] (hereinafter, also referred to as the diamine of the present invention), and therefore, the diamine of the present invention will be described first. 1 , X 1 , X 2 , Z 1 , Z 2 , R 1 and R 2 The specific examples and preferred structures of are the same as the specific examples and preferred structures shown in the description of formula [1]. In addition, in formula [3-1], W 1 As long as it is a divalent organic group represented by formula [2-1], one type may be used or two or more types may be mixed in the same polymer.
[0030] <Diamine>
[0031] The diamine of the present invention is represented by the following formula [1].
[0032]
[0033] Where Y 1 is a tetravalent organic group having an alicyclic structure, X 1 , X 2 is a divalent organic group, Z 1 , Z 2 are each independently a single bond, -NH-, or -O-, R 1 and R 2 Each independently represents an alkyl group having 1 to 5 carbon atoms.
[0034] As R 1 and R 2As the alkyl group having 1 to 5 carbon atoms, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, tert-pentyl, etc. can be listed. As the alkenyl group having 2 to 5 carbon atoms, for example, vinyl, allyl, 1-propenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, etc. can be listed. As the alkynyl group having 2 to 5 carbon atoms, for example, ethynyl, 1-propynyl, 2-propynyl (propargyl), 3-butynyl, pentynyl, etc. can be listed. Among these, from the viewpoint of liquid crystal orientation, R 1 and R 2 Preferred is a methyl group or an ethyl group, and more preferred is a methyl group.
[0035] X 1 , X 2 It is a divalent organic group, and its structure is not particularly limited, but an organic group having 30 or less carbon atoms is preferred.
[0036] Moreover, from a viewpoint of liquid crystal orientation, it is preferable to have a phenylene group.
[0037] As a particularly preferred structure, a divalent group represented by the following formula [2-2] can be mentioned.
[0038]
[0039] Where, X 3 , X 5 independently represent a phenylene group which may have a substituent; 4 represents a divalent group having 10 or less carbon atoms; L 1 , L 2 independently represent a single bond, -O-, or -S-; n1 and n2 independently represent 0 or 1; *1 and *2 represent a bonding site. 1 or Z 2 bonded to one atom and the other bonded to a nitrogen atom.
[0040] As X 3 , X 5 Specific examples of the substituent which the phenylene group may have include an alkyl group and an alkoxy group having 1 to 5 carbon atoms, a fluoroalkyl group and a fluoroalkoxy group having 1 to 5 carbon atoms, and a fluorine atom.
[0041] As X 4 Preferred specific examples of include divalent groups selected from the following (a) to (d).
[0042] (a): A group obtained by removing two hydrogen atoms from a hydrocarbon having 1 to 10 carbon atoms.
[0043] (b) A group having a structure in which a linking group selected from -O-, -S-, and -SO2- is sandwiched between one or more carbon-carbon bonds possessed by the above-mentioned (a).
[0044] (c): A group having a structure in which one or more carbon atoms in the above-mentioned (a) or (b) are replaced with silicon atoms or nitrogen atoms.
[0045] (d): A group having a structure in which one or more methylene groups (-CH2-) possessed by the above-mentioned (a) to (c) are replaced with a carbonyl group (-CO-).
[0046] The "hydrocarbon" in (a) above may be a saturated hydrocarbon or an unsaturated hydrocarbon, and may have a linear or branched chain structure, or may have a cyclic structure or a structure including a cyclic structure.
[0047] In the above (c), when a structure in which a carbon atom is replaced with a nitrogen atom is adopted, the original carbon atom is limited to a carbon atom bonded with a hydrogen atom, and in the structure after replacement with a nitrogen atom, the hydrogen atom is deleted.
[0048] As X 1 , X 2 Further preferred structures include structures represented by (X-1) to (X-11).
[0049]
[0050] (n represents an integer from 1 to 6.)
[0051] In the above formula [1], the structure of the tetravalent organic group having an alicyclic structure is not particularly limited, and specific examples thereof include the following formula [Y 1 -1]~Formula[Y 1 -20].
[0052]
[0053] Formula [Y 1 -1]~Formula[Y 1 -4], R 5 ~R 25 Each of them is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, or a phenyl group, and they may be the same or different. 5 ~R 25 A hydrogen atom, a halogen atom, a methyl group or an ethyl group is preferred, and a hydrogen atom or a methyl group is more preferred.
[0054] Among the above, the preferred formula [Y1 -1], as the formula [Y 1 -1], the specific structure can be listed as follows [Y 1 -1-1]~Formula[Y 1 From the viewpoint of the liquid crystal orientation of the liquid crystal aligning agent and the sensitivity of the photoreaction, the following formula [Y 1 -1-1] shown in the structure.
[0055]
[0056] Hereinafter, the synthesis method of diamine will be described.
[0057] The method for synthesizing the diamine of formula [1] comprises the following first step: using a tetracarboxylic acid dialkyl ester having an alicyclic structure represented by the following formula (11) as a starting material, and obtaining an amine derivative of formula (13) via an isocyanate compound of formula (12) or an isocyanate compound.
[0058] The method for obtaining the isocyanate compound of formula (12) from the tetracarboxylic acid dialkyl ester having an alicyclic structure of formula (11) includes the following methods: a method of generating a carboxylic acid azide compound (-COON3) from the carboxylic acid (-COOH) of formula (11), and forming an isocyanate compound (-NCO) through a rearrangement reaction such as Curtius rearrangement or Schmidt rearrangement; or a method of utilizing a Losen rearrangement method in which an isocyanate compound is generated from a carboxylic acid (-COOH) via a hydroxyamide derivative (-CONHOH, -CONHOTs; Ts is a tosyl group (p-toluenesulfonic acid group)). It should be noted that the isocyanate compound thus generated can form an amine derivative of formula (13) by reacting with water, tert-butyl alcohol, etc., and the compound can be directly generated from the compound of formula (11). It should be noted that R in the compound of formula (13) 31 and R 32 When it is a hydrogen atom, that is, when the diisocyanate compound of formula (12) is reacted with water, for example, by reacting an amino-protecting reagent such as di-tert-butyl dicarbonate, 4-nitrobenzyl chloride, benzyl chloroformate, fluorenylmethyl chloroformate, etc. to form an amino-protected form, purification may become easier, resulting in easier synthesis.
[0059]
[0060] In formulas (11) to (13), Y 1 is a divalent organic group having an alicyclic structure, R 1 and R 2 Each independently represents an alkyl group having 1 to 5 carbon atoms. 31 and R 32It represents a protecting group for a hydrogen atom or an amino group.
[0061] Here, as R 31 and R 32 Examples of the protecting group of the amino group include, but are not limited to, benzyl, nitrobenzyl, CBz (benzyloxycarbonyl), Boc (tert-butoxycarbonyl) and Fmoc (9-fluorenylmethoxycarbonyl).
[0062] The method for synthesizing the diamine compound of the present invention comprises: reacting an isocyanate compound of formula (12) with HZ 2 -X 2 -N 0 (Z 2 represents -O- or -NH-, X 2 Represents a divalent organic group, N 0 represents a group that can be converted into an amino group. 2 The specific examples and preferred structures of are the same as the specific examples and preferred structures shown in the description of formula [1]. A method for reacting an amine compound represented by formula (13) with an alcohol compound; or converting the amine compound of formula (13) into an active amine compound through a deprotection step as required, and reacting with Cl-C(=O)-X 2 -N 0 (X 2 Represents a divalent organic group, N 0 represents a group that can be converted into an amino group. ) represented by an acyl chloride compound, OCN-X 2 -N 0 (X 2 Represents a divalent organic group, N 0 represents a group that can be converted into an amino group. ) isocyanate compound, Cl-C(=O)-OX 2 -N 0 (X 2 Represents a divalent organic group, N 0 represents a group that can be converted into an amino group. A second step of reacting a chloroformic acid derivative represented by the following formula (14) with N 0 The group that can be converted into an amino group includes a nitro group or a protected amino group, etc. In addition, the protected amino group is not particularly limited as long as it is a group that can be easily deprotected and converted into an amino group, and includes a group formed by replacing one hydrogen of an amino group with a benzyl group, a nitrobenzyl group, a CBz group (benzyloxycarbonyl), a Boc group (tert-butoxycarbonyl), or a Fmoc group (9-fluorenylmethoxycarbonyl).
[0063]
[0064] N 0 Represents a nitro group or a protected amino group.
[0065] Specific examples of the compound of formula (14) include the following formulas (15) to (17). Here, the compound of formula (15) is a compound obtained by reacting an isocyanate compound of formula (12) with a compound having an amino group and a nitro group or a protected amino group (for example, H2N-X 2 -N 0 The compound of formula (16) is a compound produced by reacting the isocyanate compound of formula (12) with a compound having a hydroxyl group and a nitro group or a protected amino group (for example, HO-X 2 -N 0 The compound of formula (17) is a compound produced by reacting the diamide compound of formula (13) with an acid chloride compound having a nitro group or a protected amino group, or reacting with a carboxylic acid having a nitro group or a protected amino group in the presence of an appropriate condensing agent.
[0066]
[0067]
[0068] The method for synthesizing a diamine compound of the present invention comprises a third step of converting a nitro group or a protected amino group of a compound of formula (14) into an amino group, thereby producing a diamine compound of formula (1). It should be noted that in the present invention, the first step and the second step may be performed separately, but the first step and the second step may be performed continuously or as one step.
[0069] <Specific polymer A>
[0070] The specific polymer A of the present invention is at least one polymer selected from a polyimide precursor containing a structural unit represented by the following formula [3-1] and a polyimide as its imide compound, and is obtained by reacting a diamine represented by the above formula [1] with a tetracarboxylic acid derivative.
[0071]
[0072] In the formula, R 3 and R 4Each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. Examples of the alkyl group having 1 to 5 carbon atoms include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, tert-pentyl, and the like. Examples of the alkenyl group having 2 to 5 carbon atoms include vinyl, allyl, 1-propenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, and the like. Examples of the alkynyl group having 2 to 5 carbon atoms include ethynyl, 1-propynyl, 2-propynyl (propargyl), 3-butynyl, pentynyl, and the like. Among these, R 3 and R 4 A hydrogen atom, a methyl group or an ethyl group is preferred, and a hydrogen atom or a methyl group is more preferred.
[0073] V 0 V is a tetravalent organic group derived from a tetracarboxylic acid derivative, and its structure is not particularly limited. 0 The polymer may be appropriately selected based on the solubility of the polymer in the solvent, the coating properties of the liquid crystal aligning agent, the orientation of the liquid crystal when the liquid crystal aligning film is formed, the voltage holding ratio, the level of required properties such as charge storage, etc., and one type may be present in the same polymer, or two or more types may be mixed.
[0074] Examples of tetracarboxylic acid derivatives include tetracarboxylic dianhydride, tetracarboxylic acid dihalide compounds, tetracarboxylic acid dialkyl ester compounds, and tetracarboxylic acid dialkyl ester dihalide compounds. 0 Examples of tetracarboxylic dianhydride as a source of include compounds represented by the following formula [5].
[0075]
[0076] As V in formula [3-1] and formula [5] 0 Specific examples of Y include: 1 The tetravalent organic groups having an alicyclic structure shown as specific examples, and tetravalent organic groups represented by the following formulas [V-1] to [V-16], etc., but the present invention is not limited to these.
[0077]
[0078]
[0079] The specific polymer A of the present invention may contain a structural unit other than the structural unit represented by the above formula [3-1]. For example, as a structural unit other than the formula [3-1], a structural unit represented by the following formula [3-2] can be mentioned.
[0080]
[0081] Where V 0 is a tetravalent organic group derived from a tetracarboxylic acid derivative, W 2 is a divalent organic group other than the structure represented by the above formula [2-1], R 3 , R 4 , A 1 and A 2 Each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms.
[0082] V 0 , R 3 , R 4 The specific examples and preferred structures of can be the same as those of formula [3-1]. In the embodiment of the present invention, in the structural unit represented by formula [3-1] and the structural unit represented by formula [3-2], V 0 , R 3 , R 4 The specific structure does not have to be the same.
[0083] A 1 and A 2 Specific examples of the alkyl group having 1 to 5 carbon atoms include R 3 and R 4 From the perspective of liquid crystal orientation, A 1 and A 2 A hydrogen atom or a methyl group is preferred.
[0084] W 2 It is a divalent organic group derived from a diamine other than the diamine represented by the above formula [1] (hereinafter also referred to as other diamine), and its structure is not particularly limited as long as it is a divalent organic group other than the structure represented by the above formula [2-1]. Examples of other diamines include compounds represented by the following formula [2-2].
[0085]
[0086] W 2 , A 1 and A 2 Respectively represent the same as formula [3-2].
[0087] Below, we cite W 2 Specific examples of the structure are shown, but the present invention is not limited to these.
[0088]
[0089]
[0090]
[0091]
[0092]
[0093]
[0094]
[0095]
[0096] In addition, the Boc group in the formula represents a tert-butoxycarbonyl group shown below.
[0097]
[0098] When the specific polymer A contains a structural unit of the formula [3-2] in addition to the structural unit of the formula [3-1], the structural unit of the formula [3-1] is preferably 10 mol% or more, more preferably 20 mol% or more, and particularly preferably 30 mol% or more, relative to the total of the structural unit of the formula [3-1] and the structural unit of the formula [3-2].
[0099] Regarding the molecular weight of the specific polymer A, when a liquid crystal alignment film is obtained from a liquid crystal alignment agent containing the polymer, considering the strength of the coating (liquid crystal alignment film), the operability during coating formation, and the uniformity of the coating, the weight average molecular weight measured by the GPC (gel permeation chromatography, Gel Permeation Chromatography) method is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and further preferably 10,000 to 100,000.
[0100] <Method for producing polymer>
[0101] Next, the main method for producing the polymer contained in the liquid crystal aligning agent of the present invention is described. In addition, the method described below is a production example, but it is not limited to this.
[0102] For example, when the specific polymer A is a polyamic acid, the polymer is obtained by reacting tetracarboxylic dianhydride as a tetracarboxylic acid derivative with a diamine component. When polyamic acid is obtained by the reaction, a known synthesis method can be used. The synthesis method is a method for reacting tetracarboxylic dianhydride with a diamine component in an organic solvent. The method is advantageous in that it is easier to carry out in an organic solvent and does not produce by-products.
[0103] The organic solvent used in the above reaction is not particularly limited as long as the generated polyamic acid (polymer) is soluble, and examples thereof include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-methylcaprolactam, dimethyl sulfoxide, tetramethylurea, pyridine, dimethyl sulfone, hexamethyl sulfoxide, γ-butyrolactone, isopropyl alcohol, methoxymethylpentanol, dipentene, ethylpentyl ketone, methyl nonyl ketone, methyl ethyl ketone, methyl isopentyl ketone, and the like. Ketone, methyl isopropyl ketone, methyl cellosolve, ethyl cellosolve, methyl cellosolve acetate, ethyl cellosolve acetate, butyl carbitol, ethyl carbitol, ethylene glycol, ethylene glycol monoacetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, propylene glycol, propylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol tert-butyl ether, dipropylene glycol monomethyl ether, diethylene glycol, diethylene glycol monoacetate, diethylene glycol dimethyl ether, dipropylene glycol monoacetate monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monoethyl Acid monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monoacetate monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3-methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amyl acetate, butyl butyrate, butyl ether, diisobutyl ketone, methyl cyclohexene, propyl ether, dihexyl ether, dioxane, n-hexane, n-pentane, n-octane, ethyl ether, cyclohexanone, ethylene carbonate, propylene carbonate, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, N-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate, 3-methoxy methyl propionate, 3-ethoxy methyl ethyl propionate, 3-methoxy ethyl propionate, 3-ethoxy propionic acid, 3-methoxy propionic acid, 3-methoxy propyl propionate, 3-methoxy butyl propionate, diethylene glycol dimethyl ether, 4-hydroxy-4-methyl-2-pentanone, 3-methoxy-N, N-dimethyl propionamide, 3-ethoxy-N, N-dimethyl propionamide, 3-butoxy-N, N-dimethyl propionamide etc. These can be used alone or in combination. In addition, even if it is the solvent that does not dissolve polyamic acid (polymer), it is also possible to be mixed in the above-mentioned organic solvent and use in the range that the polyamic acid generated does not separate out. Particularly, the moisture in the organic solvent becomes the reason that hinders polyreaction, and then makes the polyamic acid generated hydrolyzed, so the organic solvent preferably uses the organic solvent that has been dehydrated as far as possible.
[0104] When tetracarboxylic dianhydride and diamine components are reacted in an organic solvent, the following methods can be cited: a solution obtained by dispersing or dissolving the diamine component in an organic solvent is stirred, and tetracarboxylic dianhydride is directly added, or tetracarboxylic dianhydride is dispersed or dissolved in an organic solvent and added; a method of adding diamine components to a solution obtained by dispersing or dissolving tetracarboxylic dianhydride in an organic solvent; a method of alternately adding tetracarboxylic dianhydride and diamine components, and any of these methods can be used. In addition, when tetracarboxylic dianhydride or diamine components contain a plurality of compounds, they can be reacted in a premixed state, can be reacted separately in sequence, or low molecular weight bodies obtained by separate reactions can be further mixed and reacted to form a high molecular weight body.
[0105] The polycondensation temperature at this time can be selected from any temperature of -20°C to 150°C, preferably from -5°C to 100°C. In addition, the polycondensation reaction can be carried out at any concentration. If the concentration is too low, it becomes difficult to obtain a high molecular weight polymer. If the concentration is too high, the viscosity of the reaction solution becomes too high and it is difficult to stir uniformly. Therefore, the total concentration of tetracarboxylic dianhydride and diamine components in the reaction solution is preferably set to 1 to 50% by mass, more preferably 5 to 30% by mass. The reaction can be carried out at a high concentration in the initial stage, and then an organic solvent is added.
[0106] In the polymerization reaction of polyamic acid, the total molar ratio of tetracarboxylic dianhydride to the total molar ratio of diamine components (total molar ratio of tetracarboxylic dianhydride / total molar ratio of diamine components) is preferably 0.8 to 1.2. As in a normal polycondensation reaction, the closer this molar ratio is to 1.0, the greater the molecular weight of the generated polyamic acid.
[0107] When the specific polymer A is a polyamic acid ester, it can be obtained by reacting a tetracarboxylic acid diester dichloride with a diamine component, or reacting a tetracarboxylic acid diester with a diamine component in the presence of an appropriate condensing agent or a base. Alternatively, it can be obtained by pre-synthesizing a polyamic acid by the above method, and esterifying the carboxylic acid in the amic acid by a polymer reaction.
[0108] Specifically, for example, polyamic acid ester can be synthesized by reacting tetracarboxylic acid diester dichloride and diamine in the presence of a base and an organic solvent at -20°C to 150°C, preferably 0°C to 50°C, for 30 minutes to 24 hours, preferably 1 hour to 4 hours.
[0109] As the base, pyridine, triethylamine, 4-dimethylaminopyridine, etc. can be used. Pyridine is preferred to make the reaction proceed gently. The amount of the base added is preferably 2 to 4 times the mole relative to the tetracarboxylic acid diester dichloride from the viewpoint of being an amount that is easily removed and easily obtaining a high molecular weight body.
[0110] When a tetracarboxylic acid diester and a diamine component are polycondensed in the presence of a condensing agent, as a base, triphenyl phosphite, dicyclohexylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N,N'-carbonyldiimidazole, dimethoxy-1,3,5-triazinylmethylmorpholinium, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, (2,3-dihydro-2-thioxo-3-benzoxazolyl)phosphonic acid diphenyl ester, 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)4-methoxymorpholine hydrochloride n-hydrate, etc. can be used.
[0111] In addition, in the method using the above-mentioned condensing agent, the reaction is efficiently carried out by adding a Lewis acid as an additive. As the Lewis acid, lithium halides such as lithium chloride and lithium bromide are preferred. The amount of Lewis acid added is preferably 0.1 times the molar amount to 1.0 times the molar amount of the diamine or tetracarboxylic acid diester to be reacted.
[0112] For the solvent used in the above-mentioned reaction, it can be carried out in the same solvent as the solvent used when synthesizing polyamic acid shown above, from the solubility of monomer and polymer, preferably N-methyl-2-pyrrolidone, γ-butyrolactone, these can use 1 kind or mix and use 2 kinds or more. For the concentration during synthesis, from the viewpoint of not easily causing the precipitation of polymer and easily obtaining high molecular weight body, the total concentration of tetracarboxylic acid derivatives such as tetracarboxylic acid diester dichloride, tetracarboxylic acid diester and diamine components in the reaction solution is preferably 1% by mass to 30% by mass, more preferably 5% by mass to 20% by mass. In addition, in order to prevent the hydrolysis of tetracarboxylic acid diester dichloride, the solvent used in the synthesis of polyamic acid ester is dehydrated as much as possible, preferably in a nitrogen atmosphere, to prevent the mixing of external gas.
[0113] When the specific polymer A is a polyimide, it is obtained by ring-closing imidization of a polyamic acid or polyamic acid ester as a polyimide precursor. The ring closure rate (imidation rate) of the polyimide is not necessarily 100%, and can be arbitrarily adjusted according to the application and purpose.
[0114] Examples of the method for imidizing the polyamic acid include thermal imidization in which a solution of the polyamic acid is directly heated and catalytic imidization in which a catalyst is added to a solution of the polyamic acid.
[0115] The temperature for thermally imidizing the polyamic acid in the solution is 100° C. to 400° C., preferably 120° C. to 250° C., and the imidization reaction is preferably carried out while removing water generated by the imidization reaction to the outside of the system.
[0116] The catalytic imidization of polyamic acid can be carried out by adding a basic catalyst and anhydride to a solution of polyamic acid and stirring at -20°C to 250°C, preferably 0°C to 180°C. The amount of the basic catalyst is 0.5 to 30 times by mole, preferably 2 to 20 times by mole, of the amic acid group, and the amount of the anhydride is 1 to 50 times by mole, preferably 3 to 30 times by mole, of the amic acid group. As a basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. can be cited, among which pyridine is preferred because it has a moderate alkalinity for the reaction to proceed. As anhydrides, acetic anhydride, trimellitic anhydride, pyromellitic anhydride, etc. can be cited, among which, when acetic anhydride is used, purification after the reaction is easy, so it is preferred. The imidization rate based on catalytic imidization can be controlled by adjusting the amount of catalyst, reaction temperature, and reaction time.
[0117] Moreover, as mentioned above, by heating polyamic acid ester at a high temperature, dealcoholization is promoted and it is ring-closed, and polyimide can also be obtained.
[0118] It should be noted that when the generated polyamic acid, polyamic acid ester, and polyimide are recovered from the reaction solution of polyimide precursors such as polyamic acid and polyamic acid ester, the reaction solution can be put into a poor solvent to precipitate it. As the poor solvent used in the precipitation, methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, benzene, water, etc. can be cited. The polyimide precursor and polyimide put into the poor solvent and precipitated can be filtered and recovered, and then dried at room temperature or heated under normal pressure or reduced pressure. In addition, if the operation of re-dissolving the polyimide precursor and polyimide recovered by precipitation in an organic solvent and re-precipitating and recovering is repeated 2 to 10 times, the impurities in the polymer can be reduced. As the poor solvent at this time, for example, alcohols, ketones, hydrocarbons, etc. can be cited. When more than 3 poor solvents selected from these are used, the efficiency of purification is further improved, so it is preferred.
[0119] The polymer of the present invention thus obtained can be dissolved in a predetermined organic solvent and used as a liquid crystal aligning agent. The liquid crystal aligning agent is used in a liquid crystal aligning film for controlling the alignment of liquid crystal molecules in a liquid crystal layer in a liquid crystal display element. The liquid crystal aligning agent containing the polymer of the present invention is described below.
[0120] <Liquid Crystal Alignment Agent>
[0121] The liquid crystal aligning agent of this invention contains at least 1 type of polymer selected from the said specific polymer A.
[0122] Among them, the polymer contained in the liquid crystal aligning agent of the present invention can all be the specific polymer A of the present invention, and in addition, the specific polymer A of the present invention can contain more than two different structures. Alternatively, other polymers can also be contained on the basis of the specific polymer A of the present invention. As the types of other polymers, polyamic acid, polyimide, polyamic acid ester, polyester, polyamide, polyurea, polyorganosiloxane, cellulose derivatives, polyacetals, polystyrene or its derivatives, poly (styrene-phenylmaleimide) derivatives, poly (meth) acrylates, etc. can be cited.
[0123] Among them, polyamic acid is preferred. Examples of the polyamic acid of the other polymer include a polyamic acid containing R in the above formula [3-2]: 3 , R 4 In particular, W in formula [3-2] 2 When the polyamic acid having a nitrogen-containing aromatic heterocycle and a nitrogen atom bonded to an aromatic group is mixed with the liquid crystal aligning agent of the present invention, it is preferred from the viewpoint of improving the relaxation rate of charge accumulation in the liquid crystal display element produced using the liquid crystal aligning agent of the present invention.
[0124] When the liquid crystal aligning agent of the present invention contains other polymers, the ratio of the polymer of the present invention to the total polymer components is preferably 5% by mass or more, and as one example, 5 to 95% by mass can be mentioned. The ratio of the polymer of the present invention can be appropriately selected according to the characteristics of the liquid crystal aligning agent and the liquid crystal aligning film.
[0125] The liquid crystal alignment agent of the present invention is used to make a liquid crystal alignment film, and from the viewpoint of forming a uniform film, it is usually in the form of a coating liquid. The liquid crystal alignment agent of the present invention is also preferably a coating liquid containing the aforementioned polymer component and an organic solvent that dissolves the polymer component. At this time, the concentration of the polymer in the liquid crystal alignment agent can be appropriately changed according to the setting of the thickness of the coating film to be formed. From the aspect of forming a uniform and defect-free coating film, it is preferably 1% by mass or more, and from the aspect of the storage stability of the solution, it is preferably set to 10% by mass or less. The concentration of the particularly preferred polymer is 2 to 8% by mass.
[0126] The organic solvent contained in the liquid crystal alignment agent of the present invention is not particularly limited as long as it is an organic solvent that dissolves the polymer. As a specific example, N, N-dimethylformamide, N, N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1,3-dimethyl-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, etc. can be cited. Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone are preferably used. It should be noted that the organic solvents exemplified here can be used alone or in combination. Furthermore, even if it is a solvent that does not dissolve the polymer, it can be mixed into an organic solvent and used within the range where the generated polymer does not precipitate.
[0127] In addition, the organic solvent contained in the liquid crystal aligning agent is usually a mixed solvent formed by combining the above-mentioned solvent with a solvent that improves the coating property and the surface smoothness of the coating film when the liquid crystal aligning agent is applied, and such a mixed solvent is also suitable for use in the liquid crystal aligning agent of the present invention. Specific examples of the organic solvents used in combination are given below, but are not limited to these.
[0128] For example, ethanol, isopropanol, 1-butanol, 2-butanol, isobutanol, tert-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentanol, tert-pentanol, 3-methyl-2-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 1,2-ethanediol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3- Butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol, dipropyl ether, dibutyl ether, dihexyl ether, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-butoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, ethyl 2-ethylhexyl ether, ethylene glycol monoacetate, ethylene glycol diacetate, propylene carbonate, ethylene carbonate, 2-(methoxymethoxy)ethanol, ethylene glycol monobutyl ether, ethylene glycol monoisoamyl ether, ethylene glycol monohexyl ether, 2-(hexyloxy)ethanol, furfuryl alcohol, diethylene glycol, propylene glycol, propylene glycol monobutyl ether, 1-(butoxyethoxy)propanol, propylene glycol monomethyl ether acetate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol Solvents such as alcohol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, and isopentyl lactate.
[0129] In addition to the above-mentioned solvents, for example, solvents represented by the following formulas [S-1] to [S-3] can also be used.
[0130]
[0131] In formula [S-1] and formula [S-2], R28 and R 29 represents an alkyl group having 1 to 3 carbon atoms. Examples of the alkyl group having 1 to 3 carbon atoms include methyl, ethyl, n-propyl, isopropyl, and the like. In formula [S-3], R 30 represents an alkyl group having 1 to 4 carbon atoms. Examples of the alkyl group having 1 to 4 carbon atoms include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, and tert-butyl.
[0132] Among the organic solvents used in combination, 1-hexanol, cyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, propylene glycol monobutyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monobutyl ether or dipropylene glycol dimethyl ether are preferably used. The type and content of such solvents are appropriately selected according to the coating device, coating conditions, coating environment, etc. of the liquid crystal alignment agent.
[0133] Moreover, it is preferable that these solvents are 20 mass % - 99 mass % of the whole solvent contained in a liquid crystal aligning agent. Among them, it is preferable that it is 20 mass % - 90 mass %, and it is more preferable that it is 20 mass % - 70 mass %.
[0134] The liquid crystal aligning agent of the present invention can also add components other than polymer components and organic solvents. As such additional components, a bonding aid for improving the adhesion between the liquid crystal aligning film and the substrate, the adhesion between the liquid crystal aligning film and the sealant, a cross-linking agent for improving the strength of the liquid crystal aligning film, a dielectric for adjusting the dielectric constant and resistance of the liquid crystal aligning film, a conductive material, etc. can be listed. As specific examples of these additional components, various are disclosed in the known literature related to the liquid crystal aligning agent. If one example is to be illustrated, the components disclosed in paragraphs
[0105] to
[0116] of International Publication No. 2015 / 060357 can be listed.
[0135] <Liquid crystal alignment film>
[0136] The liquid crystal alignment film of the present invention is obtained from the above-mentioned liquid crystal alignment agent. If an example of a method for obtaining a liquid crystal alignment film from a liquid crystal alignment agent is given, the following method can be cited: the liquid crystal alignment agent in the form of a coating liquid is applied to a substrate, dried and fired, and the obtained film is subjected to an alignment treatment by a brushing treatment method or a photo-alignment treatment method.
[0137] As the substrate for coating the liquid crystal aligning agent of the present invention, as long as it is a substrate with high transparency, there is no particular limitation, and plastic substrates such as acrylic substrates, polycarbonate substrates, etc. can also be used together with glass substrates and silicon nitride substrates. At this time, if a substrate with an ITO electrode or the like for driving liquid crystal is used, it is preferred from the aspect of simplification of the process. In addition, in a reflective liquid crystal display element, if it is only a single-sided substrate, an opaque object such as a silicon wafer can also be used, and the electrode in this case can also use a material that reflects light such as aluminum.
[0138] The coating method of the liquid crystal aligning agent is not particularly limited, and is generally industrially screen printing, offset printing, flexographic printing, inkjet printing, etc. Other coating methods include dipping, roll coating, slit coating, spin coating, spraying, etc., and these methods can be used according to the purpose.
[0139] The firing after the liquid crystal alignment agent is applied to the substrate is carried out at 50 to 300°C, preferably 80 to 250°C, by heating means such as a hot plate, a hot air circulation furnace, and an infrared furnace, so that the solvent can be evaporated to form a coating (liquid crystal alignment film). If the thickness of the coating formed after firing is too thick, it is disadvantageous in terms of power consumption of the liquid crystal display element. If it is too thin, the reliability of the liquid crystal display element is sometimes reduced, so it is preferably 5nm to 300nm, and more preferably 10nm to 100nm. In the case of horizontally oriented or tilted orientation of the liquid crystal, the fired coating is treated by brushing or polarized ultraviolet irradiation.
[0140] After the liquid crystal alignment agent is applied to the substrate, the solvent is evaporated by heating means such as a hot plate, a heat circulation oven, an IR (infrared) oven, etc., and then fired. The drying and firing steps after the liquid crystal alignment agent is applied can be selected at any temperature and time. Usually, in order to fully remove the contained solvent, the conditions of firing at 50°C to 120°C for 1 minute to 10 minutes and then firing at 150°C to 300°C for 5 minutes to 120 minutes can be listed.
[0141] The liquid crystal aligning film of the present invention is suitable as a liquid crystal aligning film of a liquid crystal display element of a transverse electric field system such as an IPS system or an FFS system, and is particularly useful as a liquid crystal aligning film of a liquid crystal display element of an FFS system.
[0142] <Liquid Crystal Display Element>
[0143] The liquid crystal display element of the present invention has the above-mentioned liquid crystal alignment film, and after obtaining a substrate with a liquid crystal alignment film obtained by the above-mentioned liquid crystal alignment agent, a liquid crystal cell is prepared by a known method, and the element is prepared using the liquid crystal cell. As an example, it is a liquid crystal display element having the following liquid crystal cell, wherein the liquid crystal cell has: two substrates arranged in a relative manner, a liquid crystal layer provided between the substrates, and a liquid crystal alignment film formed by the liquid crystal alignment agent of the present invention provided between the substrates and the liquid crystal layer.
[0144] The substrate used in the liquid crystal display element of the present invention is not particularly limited as long as it is a highly transparent substrate, and is generally a substrate on which a transparent electrode for driving liquid crystal is formed. As a specific example, the same substrate as the substrate described in the above-mentioned liquid crystal alignment film can be cited.
[0145] Moreover, the liquid crystal aligning film is formed by applying the liquid crystal aligning agent of this invention on this substrate, and baking it, and the detail is as mentioned above.
[0146] The liquid crystal material constituting the liquid crystal layer of the liquid crystal display element of the present invention is not particularly limited, and nematic liquid crystal and smectic liquid crystal can be cited, wherein nematic liquid crystal is preferred, and any of positive liquid crystal material and negative liquid crystal material can be used. Specifically, for example, MLC-2003, MLC-6608, MLC-6609, MLC-3019, MLC-2041, MLC-7026-100, etc. manufactured by Merck can be used.
[0147] Specifically, transparent glass substrates are prepared, a common electrode is provided on one substrate, and a segment electrode is provided on the other substrate. These electrodes can be, for example, ITO electrodes, and can be patterned so as to realize the desired image display. Next, an insulating film is provided on each substrate in a manner covering the common electrode and the segment electrode. The insulating film can be, for example, a film containing SiO2-TiO2 formed by a sol-gel method. Next, a liquid crystal alignment film is formed on each substrate under the conditions described above.
[0148] Next, a UV-curable sealant, for example, is arranged at a specified position on one of the two substrates on which a liquid crystal alignment film is formed, and liquid crystals are further arranged at a plurality of specified locations on the surface of the liquid crystal alignment film. The other substrate is then bonded and crimped so that the liquid crystal is opposite to the liquid crystal alignment film, thereby spreading the liquid crystal in front of the liquid crystal alignment film. The entire surface of the substrate is irradiated with ultraviolet rays to cure the sealant, thereby obtaining a liquid crystal unit.
[0149] Alternatively, as a process after forming a liquid crystal alignment film on a substrate, when a sealant is arranged at a predetermined position on one substrate, an opening that can be filled with liquid crystal from the outside is pre-arranged, and after the substrates are attached without arranging liquid crystals, a liquid crystal material is injected into the liquid crystal cell through the opening provided in the sealant, and then the opening is sealed with an adhesive to obtain a liquid crystal cell. The injection of the liquid crystal material can be a vacuum injection method or a method using a capillary phenomenon in the atmosphere.
[0150] In any of the above methods, in order to ensure a space for filling the liquid crystal material in the liquid crystal cell, it is preferred to provide columnar protrusions on one substrate, scatter spacers on one substrate, mix spacers in the sealant, or use a combination of these.
[0151] Next, polarizing plates are provided. Specifically, it is preferred that a pair of polarizing plates be attached to the surfaces of the two substrates on the opposite sides to the liquid crystal layer.
[0152] It should be noted that the liquid crystal alignment film and the liquid crystal display element of the present invention are not limited to the above description as long as the liquid crystal alignment agent of the present invention is used, and can also be produced by other known methods. The process of obtaining the liquid crystal display element from the liquid crystal alignment agent is disclosed in paragraphs
[0074] to
[0081] of Japanese Patent Publication No. 2015-135393, for example, and is also disclosed in many documents.
[0153] As described above, the liquid crystal display element produced using the liquid crystal aligning agent of the present invention has excellent reliability and can be suitably used for a large-screen high-definition liquid crystal television and the like.
[0154] Example
[0155] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to these Examples.
[0156] The chemical structural formulas of the general solvents for dissolving the materials used in the examples and the monomers as raw materials of the materials used in the examples are shown below.
[0157] NMP: N-methyl-2-pyrrolidone
[0158] GBL: gamma-butyrolactone
[0159] BCS: Butyl Cellosolve
[0160] DC-1: 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride
[0161] DC-2: Bicyclo[3,3,0]octane-2,4,6,8-tetracarboxylic dianhydride
[0162] DC-3: 1,2,3,4-cyclobutanetetracarboxylic dianhydride
[0163] DC-4: Pyromellitic anhydride
[0164] DC-5: Tetrahydro-1H-5,9-methanopyrano[3,4-d]oxazoline-1,3,6,8(4H)-tetraone
[0165] DA-1: 2,4-bis((4-aminobenzamide)cyclobutane-1,3-dicarboxylic acid dimethyl ester
[0166] DA-2: 2,4-bis((4-aminophenyl)carbamoyl)cyclobutane-1,3-dicarboxylic acid dimethyl ester
[0167] DA-3: 1,2-bis(4-aminophenoxy)ethane
[0168] DA-4: 1,2-bis(4-aminophenoxy)hexane
[0169] DA-5: 1-tert-Butyloxycarbonyl-1,3-bis(4-aminophenethyl)urea
[0170] DA-6: 2,4-bis((4-aminophenyl)ureido)cyclobutane-1,3-dicarboxylic acid dimethyl ester
[0171]
[0172] The synthesis methods of the materials used in the Examples and the measurement methods of the properties are as follows.
[0173] [Viscosity]
[0174] In the synthesis example, the viscosity of the polyamic acid solution was measured using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) with a sample amount of 1.1 mL, a conical rotor TE-1 (1°34', R24), and a temperature of 25°C.
[0175] [Molecular weight]
[0176] The molecular weight was measured using a GPC (normal temperature gel permeation chromatography) apparatus, and the number average molecular weight (Mn) and the weight average molecular weight (Mw) were calculated as polyethylene glycol and polyethylene oxide equivalent values.
[0177] GPC apparatus: Shodex (GPC-101), column: Shodex (KD803, KD805 in series), column temperature: 50°C, eluent: N,N-dimethylformamide (as additives, lithium bromide monohydrate (LiBr·H2O) 30 mmol / L, phosphoric acid·anhydrous crystals (orthophosphoric acid) 30 mmol / L, tetrahydrofuran (THF) 10 ml / L), flow rate: 1.0 ml / min
[0178] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide manufactured by Tosoh Corporation (weight average molecular weight (Mw) of about 900,000, 150,000, 100,000, 30,000), and polyethylene glycol manufactured by Polymer Laboratories Ltd. (peak top molecular weight (Mp) of about 12,000, 4,000, 1,000). In order to avoid peak overlap, two samples, a sample in which four types of 900,000, 100,000, 12,000, and 1,000 were mixed, and a sample in which three types of 150,000, 30,000, and 4,000 were mixed, were measured separately.
[0179] [Determination of Imidization Ratio]
[0180] 20 mg of polyimide powder was placed in an NMR sample tube (NMR sampling tube standard, (manufactured by Kusano Scientific Co., Ltd.)), deuterated dimethyl sulfoxide (DMSO-d6, 0.05% TMS (tetramethylsilane) mixed product) (0.53 ml) is added, and ultrasonic waves are applied to completely dissolve it. The solution is measured with a 500 MHz proton NMR using an NMR measuring instrument (JNW-ECA500) (manufactured by JEOL DATUM LTD.). For the imidization rate, the proton derived from the structure that does not change before and after the imidization is determined as the reference proton, and the peak accumulation value of the proton and the proton peak accumulation value derived from the NH group of the amic acid appearing near 9.5 ppm to 11.0 ppm are used to calculate it by the following formula. Among them, the imidization rate calculated by the following formula adopts the value when the proton peak derived from the NH group contained in the monomer that does not participate in the polymerization reaction is excluded.
[0181] Imidization rate (%) = (1-α·x / y) × 100
[0182] In the above formula, x is the peak cumulative value of protons derived from NH groups of amic acid, y is the peak cumulative value of reference protons, and α is the ratio of the number of reference protons to NH protons of one amic acid in the case of polyamic acid (imidation ratio 0%).
[0183] [Fabrication of liquid crystal cell for FFS mode]
[0184] A liquid crystal cell having a configuration of a fringe field switching (FFS) mode liquid crystal display element was produced.
[0185] First, prepare a substrate with electrodes. The substrate is a glass substrate with a size of 30mm×35mm and a thickness of 0.7mm. An ITO electrode with a solid pattern is formed on the substrate as the first layer constituting the counter electrode. A SiN (silicon nitride) film formed by a CVD method is formed as the second layer on the counter electrode of the first layer. The film thickness of the second layer SiN film is 500nm, and it functions as an interlayer insulating film. On the second layer SiN film, as the third layer, a comb-shaped pixel electrode formed by patterning the ITO film is arranged to form two pixels, the first pixel and the second pixel. The size of each pixel is about 10mm in the vertical direction and about 5mm in the horizontal direction. At this time, the counter electrode of the first layer and the pixel electrode of the third layer are electrically insulated by the action of the SiN film of the second layer.
[0186] The pixel electrode of the third layer has a comb-like shape formed by arranging a plurality of electrode elements in the shape of a Chinese character "く" with a bent central portion. The width of each electrode element in the short side direction is 3μm, and the interval between the electrode elements is 6μm. The pixel electrode forming each pixel is composed of a plurality of electrode elements in the shape of a Chinese character "く" with a bent central portion, so the shape of each pixel is not a rectangular shape, but has a shape similar to a thick Chinese character "く" that is bent in the central portion like the electrode elements. Moreover, each pixel is divided into upper and lower parts with the bent portion in the center as the boundary, and has a first area on the upper side of the bent portion and a second area on the lower side.
[0187] When the first area and the second area of each pixel are compared, the electrode elements of the pixel electrodes constituting them are formed in different directions. That is, with the polarization direction of the linearly polarized ultraviolet (LPUV) light of the liquid crystal alignment film described later as a reference, the electrode elements of the pixel electrode in the first area of the pixel are formed to form an angle of +80° (clockwise), and the electrode elements of the pixel electrode in the second area of the pixel are formed to form an angle of -80° (counterclockwise). That is, in the first area and the second area of each pixel, the directions of the rotation action (in-plane switching) of the liquid crystal in the substrate surface induced by the application of the voltage between the pixel electrode and the counter electrode are opposite to each other.
[0188] Next, the liquid crystal alignment agent was filtered with a 1.0 μm filter, and then applied by spin coating on the prepared substrate with electrodes and a glass substrate with a columnar spacer of 4 μm in height formed on the back with an ITO film. Drying was performed on a hot plate at 80°C for 2 minutes, and the coating surface was irradiated with ultraviolet rays of 254 nm with a linear polarization having an extinction ratio of 26:1 or more with the aid of a polarizing plate, and then calcined in a hot air circulation oven at 230°C for 30 minutes to form a coating with a film thickness of 100 nm. The above two substrates were set as a group, and a sealant was printed on the substrate. After the other substrate was attached in a manner that the orientation direction facing the liquid crystal alignment film surface became 0°, the sealant was cured to produce an empty unit. Liquid crystal MLC-3019 (Merck) was injected into the empty unit by a reduced pressure injection method, and the injection port was sealed to obtain an FFS driven liquid crystal unit.
[0189] [Afterimage Evaluation]
[0190] The polarizing plates are arranged in such a way that the angle formed by the two polarizing plates is 90°, and this state is set as a cross prism. The above-mentioned liquid crystal unit for afterimage evaluation is arranged between the two polarizing plates, and the orientation state of the injected liquid crystal is observed. For the specific evaluation method, it is judged by observing whether the injected liquid crystal is uniformly oriented in the liquid crystal unit. When the liquid crystal in the liquid crystal unit is unevenly oriented, bright lines can be seen, and a clear light / dark field of view cannot be observed according to the angle formed by the orientation direction of the two polarizing plates and the liquid crystal. On the other hand, when the liquid crystal in the liquid crystal unit is uniformly oriented, no bright lines can be seen, and a clear light / dark field of view can be observed according to the angle formed by the orientation direction of the two polarizing plates and the liquid crystal. As an evaluation standard, it will be recorded as "good" when the above-mentioned bright lines are not seen at all and a clear light / dark field of view can be observed, it will be recorded as "acceptable" when a clear light / dark field of view can be observed but a bright line can be slightly seen, and it will be recorded as "poor" when a clear light / dark field of view cannot be observed and a clear bright line can be seen.
[0191] [Indicates a bad review]
[0192] The liquid crystal cell prepared in the above was evaluated for poor performance. The evaluation was performed by heating the liquid crystal cell prepared in the above in a heating oven at 60°C for more than 2 weeks and then observing it with a polarizing microscope (ECLIPSE E600WPOL) (manufactured by NIKON CORPORATION). Specifically, the liquid crystal cell was set with a cross prism relative to the polarizing plate, and observed with a polarizing microscope with a lens magnification set to 5 times, and the number of bright spots confirmed was counted, and a number of bright spots less than 5 was recorded as "good", and 5 or more was recorded as "bad".
[0193] [Evaluation of Liquid Crystal Orientation]
[0194] The orientation of the liquid crystal unit produced in the above was evaluated. As an evaluation method, the liquid crystal unit was configured to have the minimum brightness under the polarizing plate cross prism, and the orientation state was compared just after production and after re-orientation treatment (heating at 110°C for 1 hour and returning to room temperature). The case where no flow orientation, domain, etc. were observed just after the liquid crystal unit was produced was recorded as 0, the case where the flow orientation, domain, etc. disappeared by re-orientation treatment was recorded as △, and the case where the aforementioned orientation defects were observed after re-orientation was recorded as ×.
[0195] "Monomer Synthesis Example"
[0196] Synthesis Example 1 Synthesis of dimethyl 2,4-bis(3-(4-aminophenyl)ureido)cyclobutane-1,3-dicarboxylate
[0197]
[0198] <1st step>
[0199] Synthesis of Dimethyl 2,4-Bis(3-(4-nitrophenyl)ureido)cyclobutane-1,3-dicarboxylate
[0200] In a 1L four-necked flask equipped with a nitrogen inlet tube, bis(methoxycarbonyl)cyclobutane-1,3-dicarboxylic acid (100.0 g: 384.23 mmol) was weighed, toluene (500.0 g) was added, triethylamine (97.2 g: 960.58 mmol), diphenylphosphoryl azide [DPPA] (232.6 g: 845.31 mmol) was added, and after stirring at room temperature for 30 minutes under a nitrogen atmosphere, the temperature was raised to 60°C and the reaction was further carried out for 3 hours. As the reaction proceeded, gas was generated, and it was confirmed that the generation of gas had stopped. The reaction solution was returned to room temperature, 1,4-diaza-bicyclo[2.2.2]octane [DABCO] (2.15 g: 19.21 mmol), 4-nitroaniline (116.76 g: 845.31 mmol), tetrahydrofuran (200.0 g) were added, and the temperature was raised to 60°C again, and the reaction was carried out for 24 hours under a nitrogen atmosphere. After confirming the disappearance of the raw materials by TLC, the reaction solution was transferred to a separatory funnel. At this time, the organic layer was divided into two layers, so the lower layer was separated and solids precipitated when it was put into methanol for stirring. The solid was recovered by filtration. The upper layer on one side was washed three times with 100 ml of pure water, and the organic layer was distilled to remove the solvent using a rotary evaporator, resulting in solid precipitation. The crude product was recovered and mixed with the solid obtained above, and heated and washed twice with methanol (300.0 g) (reflux: 1 hour), and vacuum dried to obtain a light yellow solid (136.56 g: yield 67%). The structure was confirmed by nuclear magnetic resonance spectroscopy [ 1H-NMR (400 MHz)], it was confirmed to be the target substance. The measurement data are shown below.
[0201] 1 H-NMR (400MHz: D6-DMSO) δ: 9.34 (s: 2H), 8.11 (q: 4H), 7.60 (q: 4H), 7.04 (d: 2H), 4.78 (q: 2H), 4.07 (m: 2H), 3.60 (s: 6H)
[0202] <Step 2>
[0203] Synthesis of Dimethyl 2,4-Bis(3-(4-aminophenyl)ureido)cyclobutane-1,3-dicarboxylate
[0204] In a 1L 4-necked flask, 2,4-bis(3-(4-nitro-phenyl)ureido)-cyclobutane-1,3-dicarboxylic acid dimethyl ester (100.0g: 188.52mmol) obtained by the above operation, 10% palladium on carbon (10.0g), and fully degassed N,N-dimethylformamide (500.0g) were added to replace the hydrogen gas, and the reaction was carried out for 24 hours with strong stirring at 60°C. After confirming the disappearance of the raw materials, the palladium on carbon was removed by filtration in a hot state, and then activated carbon (30g) was added, stirred at 60°C for 3 hours, and hot filtered. The filtrate was poured into 1L of methanol, and after stirring at 10°C for a while, a solid precipitated. The solid was recovered by filtration, heated and washed twice with 300.0g of methanol, and vacuum dried to obtain 74.5g of the target milky white solid. The structure was confirmed by nuclear magnetic resonance spectroscopy [ 1 H-NMR (400 MHz)], it was confirmed to be the target substance. The measurement data are shown below.
[0205] 1 H-NMR (400MHz: D6-DMSO) δ: 8.01 (s: 4H), 6.95 (q: 4H), 6.49 (d: 2H), 6.45 (q: 4H), 4.75 (q: 2H), 4.73 (br: 4H), 3.64 (s: 6H), 3.35 (m: 2H)
[0206] Synthesis example 2
[0207] Synthesis of 2,4-bis(4-aminobenzamido)cyclobutane-1,3-dicarboxylic acid dimethyl ester
[0208]
[0209] <1st step>
[0210] Synthesis of Dimethyl 2,4-Bis((tert-Butoxycarbonyl)amino)cyclobutane-1,3-dicarboxylate
[0211] In a 2L four-necked flask equipped with a nitrogen inlet tube, bis(methoxycarbonyl)cyclobutane-1,3-dicarboxylic acid (100 g: 418 mmol) was weighed, toluene (1000 g) was added, triethylamine (92.0 g: 916 mmol), diphenylphosphoryl azide [DPPA] (252 g: 916 mmol) was added, and after stirring at room temperature for 30 minutes under a nitrogen atmosphere, the temperature was raised to 60°C and the reaction was further carried out for 3 hours. As the reaction proceeded, gas was generated, and it was confirmed that the generation of gas had stopped. The reaction solution was cooled to room temperature, and 1,4-diaza-bicyclo[2.2.2]octane [DABCO] (2.35: 20.9 mmol), tert-butyl alcohol (155 g: 2.09×10 3 mmol), heated to 80°C, and heated and stirred for 24 hours under a nitrogen atmosphere. After the reaction was completed, the reaction solution was cooled at -20°C to recrystallize the product. The solid was recrystallized using ethyl acetate as a good solvent and hexane as a poor solvent, and vacuum dried to obtain the target white solid (60.0 g: 145 mmol, yield: 35%). The structure of the product was confirmed by nuclear magnetic resonance spectroscopy [ 1 H-NMR (400 MHz)], it was confirmed to be the target substance. The measurement data are shown below.
[0212] 1 H-NMR (400MHz: D6-DMSO) δ: 7.40-7.38 (ss: 2H), 4.51-4.49 (q: 2H), 3.56 (s: 6H), 3.42-3.38 (q: 2H), 1.36 (s: 18H)
[0213] <Step 2>
[0214] Synthesis of 2,4-bis(4-nitrobenzamido)cyclobutane-1,3-dicarboxylic acid dimethyl ester
[0215] In a 2 L four-necked flask equipped with a nitrogen inlet tube, 2,4-bis((tert-butoxycarbonyl)amino)cyclobutane-1,3-dicarboxylic acid dimethyl ester (60.0 g: 145 mmol) obtained by the above operation was weighed, chloroform (600.0 g) was added, and trifluoroacetic acid [TFA] (164 g: 1.45 × 10 3mmol), heated and stirred at 40°C for 12 hours. The reaction solution was cooled to about 0°C, triethylamine (32.1 g: 318 mmol) was added, and the mixture was stirred at room temperature for 0.5 hours. Thereafter, 4-nitrobenzoyl chloride (67.0 g: 602 mmol) dissolved in 670 g of chloroform was gently added dropwise, and the mixture was stirred at room temperature for 6 hours. After the reaction, the reaction solution was concentrated, washed three times with 200 ml of pure water, and once with 200 ml of saturated brine. Thereafter, the mixture was recrystallized using chloroform as a good solvent and hexane as a poor solvent, and the obtained solid was vacuum dried to obtain 56.0 g (112 mmol) of the target light yellow solid. The structure of the product was confirmed by nuclear magnetic resonance spectroscopy. 1 H-NMR (400 MHz)], it was confirmed to be the target substance. The measurement data are shown below.
[0216] 1 H-NMR (400MHz: D6-DMSO) δ: 9.29-9.27 (d: 2H), 8.37 (dd: 4H), 8.06 (dd: 4H), 5.23-5.17 (m: 2H), 3.86-3.82 (m: 2H), 3.55 (s: 6H)
[0217] <Step 3>
[0218] Synthesis of 2,4-bis(4-aminobenzamido)cyclobutane-1,3-dicarboxylic acid dimethyl ester
[0219] In a 1L 4-necked flask, add dimethyl 2,4-bis(4-nitrobenzamido)cyclobutane-1,3-dicarboxylate (20.0 g: 112 mmol) obtained by the above operation, activated carbon loaded with 10% palladium (11.2 g), and fully degassed N,N-dimethylformamide (500 g), fill and replace the system with hydrogen, and stir vigorously at room temperature for 48 hours. After the reaction is completed, remove the palladium carbon and concentrate the N,N-dimethylformamide under reduced pressure. Dissolve the precipitated solid in a minimum amount of DMF and recrystallize it using hexane as a poor solvent. Disperse the obtained solid in methanol and heat and stir at 80°C for 6 hours. Thereafter, recover the solid by filtration and dry it under reduced pressure to obtain the target white solid (35.0 g: 79.5 mmol, yield: 71%). The structure was confirmed by nuclear magnetic resonance spectroscopy [ 1 H-NMR (400 MHz)], it was confirmed to be the target substance. The measurement data are shown below.
[0220] 1H-NMR (400MHz: D6-DMSO) δ: 8.36-8.34 (dd: 2H), 7.56-7.53 (q: 4H), 6.55-6. 52 (q: 4H), 5.65 (br: 4H), 5.14-5.08 (q: 2H), 3.76-3.72 (q: 2H), 3.49 (s: 6H)
[0221] [Synthesis example 1]
[0222] In a 50mL four-necked flask with a stirring device and a nitrogen inlet tube, 5.06g (11.5mmol) of DA-1 was taken, 20.3g of NMP was added, and the mixture was heated and stirred at 70°C for 30 minutes while nitrogen was supplied to dissolve it. After the diamine solution was cooled to room temperature by water cooling, 2.37g (11.3mmol) of DC-1 was added while stirring, and 9.50g of NMP was further added, and the mixture was heated and stirred at 40°C for 24 hours to obtain a solution of polyamic acid (PAA-1). The viscosity of the polyamic acid solution at a temperature of 25°C was 300mPa·s. In addition, the molecular weight and molecular weight distribution of the polyamic acid were Mn=1.27×10 4 , Mw=3.07×10 4 , Mw / Mn=2.41.
[0223] [Synthesis Examples 2, 3, 4, 5, 6]
[0224] The diamine components, tetracarboxylic acid components, and NMP shown in Table 1 below were used, and the reaction temperature and solid content concentration were carried out in the same manner as in Synthesis Example 1, thereby obtaining polyamic acid solutions PAA-2, PAA-3, PAA-4, PAA-5, and PAA-6 shown in Table 1 below. In addition, the viscosity and molecular weight of the obtained polyamic acid are shown in Table 2 below.
[0225] [Table 1]
[0226]
[0227] [Table 2]
[0228]
[0229] [Synthesis Example 7]
[0230] In a 100ml four-necked flask with a stirring device and a nitrogen inlet tube, 55.0g of the obtained polyamic acid solution (PAA-1) was taken, 18.3g of NMP was added, and stirred at room temperature for 30 minutes. 5.12g (50.7mmol) of acetic anhydride and 1.59g (20.1mmol) of pyridine were added to the obtained polyamic acid solution, and heated and stirred for 6 hours at 55°C for chemical imidization. The obtained reaction solution was put into 218ml of methanol while stirring, and the precipitated precipitate was recovered, and then washed 3 times with 218ml of methanol. The obtained resin powder was dried at 60°C for 12 hours to obtain a polyimide resin powder (PIP-1). The imidization rate of the polyimide resin powder is more than 95%.
[0231] [Synthesis example 8]
[0232] Chemical imidization was carried out using the polyamic acid solution (PAA-2) by the same procedure as in Synthesis Example 7 with respect to the amounts of acetic anhydride and pyridine introduced and the reaction temperature. However, a gel-like solid component was precipitated during heating and stirring, and chemical imidization could not be carried out accurately.
[0233] [Synthesis Example 9]
[0234] In a 50ml four-necked flask with a stirring device and a nitrogen inlet tube, 24.0g of the obtained polyamic acid solution (PAA-3) was taken, 8.00g of NMP was added, and stirred at room temperature for 30 minutes. 2.56g (25.0mmol) of acetic anhydride and 1.19g (15.1mmol) of pyridine were added to the obtained polyamic acid solution, and heated and stirred for 4 hours at 55°C for chemical imidization. The obtained reaction solution was put into 107ml of methanol while stirring, and the precipitated precipitate was recovered, and then washed 3 times with 107ml of methanol. The obtained resin powder was dried at 60°C for 12 hours to obtain a polyimide resin powder (PIP-3). The imidization rate of the polyimide resin powder is more than 95%.
[0235] [Synthesis Example 10]
[0236] In a 50ml four-necked flask with a stirring device and a nitrogen inlet tube, 18.0g of the obtained polyamic acid solution (PAA-3) was taken, 6.00g of NMP was added, and stirred for 30 minutes at room temperature. 0.77g (7.53mmol) of acetic anhydride and 0.30g (3.80mmol) of pyridine were added to the obtained polyamic acid solution, and heated and stirred for 2 hours at 55°C for chemical imidization. The obtained reaction solution was put into 75.2ml of methanol while stirring, and the precipitated precipitate was recovered, and then washed 3 times with 75.2ml of methanol. The obtained resin powder was dried at 60°C for 12 hours to obtain a polyimide resin powder (PIP-4). The imidization rate of the polyimide resin powder was 73%.
[0237] [Synthesis Example 11]
[0238] In a 50ml four-necked flask with a stirring device and a nitrogen inlet tube, 44.0g of the obtained polyamic acid solution (PAA-4) was taken, 14.7g of NMP was added, and stirred at room temperature for 30 minutes. 4.50g (44.1mmol) of acetic anhydride and 2.09g (26.5mmol) of pyridine were added to the obtained polyamic acid solution, and heated and stirred for 2 hours at 55°C for chemical imidization. The obtained reaction solution was put into 196ml of methanol while stirring, and the precipitated precipitate was recovered, and then washed 3 times with 196ml of methanol. The obtained resin powder was dried at 60°C for 12 hours to obtain a polyimide resin powder (PIP-5). The imidization rate of the polyimide resin powder is more than 95%.
[0239] [Synthesis Example 12]
[0240] In a 100ml four-necked flask with a stirring device and a nitrogen inlet tube, 96.5g of the obtained polyamic acid solution (PAA-5) was taken, 32.2g of NMP was added, and stirred at room temperature for 30 minutes. Acetic anhydride 7.03g (68.9mmol) and 3.64g (46.0mmol) of pyridine were added to the obtained polyamic acid solution, and heated and stirred for 2 hours at 55°C for chemical imidization. The obtained reaction solution was put into 433ml of methanol while stirring, and the precipitated precipitate was recovered, and then washed 3 times with 433ml of methanol. The obtained resin powder was dried at 60°C for 12 hours to obtain a polyimide resin powder (PIP-6). The imidization rate of the polyimide resin powder was 62%.
[0241] [Synthesis Example 13]
[0242] Using the polyamic acid solution (PAA-6), chemical imidization was carried out in the same manner as in Synthesis Example 12 with respect to the amounts of acetic anhydride and pyridine introduced and the reaction temperature, thereby obtaining a polyimide resin powder (PIP-7). The imidization ratio of the polyimide resin powder was 68%.
[0243] The imidization ratios of the polyimide resin powders obtained in Synthesis Examples 7, 8, 9, 10, 11, 12, and 13 are shown in Table 3 below.
[0244] [Table 3]
[0245]
[0246] [Synthesis Example 14]
[0247] 5.56 g of polyimide resin powder (PIP-1) was taken into a 50 ml eggplant flask, and 40.7 g of NMP was added in a manner that the solid content concentration became 12%. The mixture was stirred and dissolved at 70°C for 24 hours to obtain a polyimide solution (PIS-1). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution. The molecular weight and molecular weight distribution of the polyimide solution were Mn=1.30×10 4 , Mw=3.35×10 4 , Mw / Mn=2.56.
[0248] [Synthesis Example 15]
[0249] Using the polyimide resin solid (PIP-2), a polyimide solution (PIS-2) was obtained by the same method as in Synthesis Example 14. However, unnecessary substances were generated, and a uniform polyimide solution could not be obtained.
[0250] [Synthesis Examples 16, 17, 18, 19, 20]
[0251] Using polyimide resin powders (PIP-3, PIP-4, PIP-5, PIP-6, PIP-7), polyimide solutions (PIS-3, PIS-4, PIS-5, PIS-6, PIS-7) were obtained by the same method as in Synthesis Example 14. In addition, the molecular weights of the obtained polyimide solutions are shown in Table 4 below.
[0252] [Table 4]
[0253]
[0254] When the polyamic acid solution obtained by sequentially polymerizing DA-1 or DA-2 and DC-1 was chemically imidized, the polyamic acid containing DA-1 could normally undergo chemical ring closure, but the polyamic acid containing DA-2 precipitated a gel-like solid component during the chemical ring closure and could not be evaluated.
[0255] By using the DA-1 analog included in the present claim, the solubility in solvents is specifically better when the polyamic acid is made and the polyimide is formed by chemically closing the ring. In addition, PIS-1, PIS-3, PIS-4, and PIS-5, which are materials included in the present claim, show properties that can withstand practical use as a liquid crystal alignment film, and can further reduce the risk of poor performance, and are therefore shown below.
[0256] [Synthesis Example 21]
[0257] In a 20 ml sample tube with a stirrer, 6.50 g of the polyimide solution (PIS-1) obtained in Synthesis Example 1 was taken, 1.00 g of NMP, 3.53 g of GBL solution, and 3.00 g of BCS were added, and stirred for 2 hours with a magnetic stirrer to obtain a liquid crystal aligning agent (A-1). The liquid crystal aligning agent (A-1) was used to evaluate the liquid crystal orientation and prepare a liquid crystal cell for bright spot evaluation according to the steps shown below.
[0258] [Synthesis example 22]
[0259] Liquid crystal aligning agents (A-2, A-3, A-4, A-5, A-6, A-7) were obtained by the same method as in Synthesis Example 21 using polyimide solutions (PIS-3, PIS-4, PIS-5, PIS-6, PIS-7).
[0260] Using this liquid crystal aligning agent (A-2, A-3, A-4, A-5, A-6, A-7), liquid crystal orientation evaluation and preparation of a liquid crystal cell for bright spot evaluation were performed by the procedure shown below.
[0261] [Example 1]
[0262] The liquid crystal aligning agent (A-1) obtained in Synthesis Example 21 was filtered through a 1.0 μm filter, and then applied to a 30 mm × 40 mm ITO substrate by spin coating, and dried on a hot plate at 80° C. for 2 minutes. The coating surface was exposed to a light beam at 0.15 J / cm 2 Up to 0.40J / cm 2After irradiating with ultraviolet rays of 254nm wavelength with linear polarization and extinction ratio of 26:1 at various exposure amounts between, the substrate was sintered in a hot air circulation oven at 230°C for 17 minutes to obtain a substrate with a liquid crystal orientation film. The above two substrates obtained are set as a group, and a sealant is printed on the substrate. Another substrate is attached in a manner that the liquid crystal orientation film faces each other and the orientation direction becomes 0°, and then the sealant is cured to produce an empty unit. Liquid crystal MLC-3019 (manufactured by Merck) is injected into the empty unit by a reduced pressure injection method, and the injection port is sealed to obtain a liquid crystal orientation liquid crystal unit. The evaluation results of each afterimage are shown in Table 5 below. It should be noted that the liquid crystal orientation is evaluated based on the aforementioned evaluation criteria.
[0263] [Examples 2, 3, 4]
[0264] Liquid crystal cells for image sticking evaluation were prepared by using each liquid crystal aligning agent (A-2, A-3, A-4) instead of the liquid crystal aligning agent (A-1) and changing the ultraviolet irradiation amount and the calcination temperature to the same method as in Example 1. The image sticking evaluation results are shown in Table 5 below.
[0265] [Comparative Examples 1 and 2]
[0266] Liquid crystal cells for image sticking evaluation were prepared by using each liquid crystal aligning agent (A-5, A-6) instead of the liquid crystal aligning agent (A-1) and changing the irradiation amount of ultraviolet rays and the calcining temperature to the same method as in Example 1. Each image sticking evaluation result is shown in Table 5 below.
[0267] [Table 5]
[0268]
[0269] The liquid crystal aligning agents (A-1, A-2, A-3, A-4) comprising DA-1 and DC-1 described in the claims were exposed to light at an exposure dose of 0.10 J / cm 2 Up to 0.40J / cm 2 In addition, the copolymerized polyimide using DA-1 and other types of diamine components and DC-1 also showed good afterimage characteristics. The quality of the afterimage characteristics and the exposure amount vary depending on the combined diamine components. As an example, the liquid crystal aligning agent (A-2) obtained by copolymerizing DA-1 and DA-3 has an exposure of 0.10 J / cm 2 Up to 0.40J / cm 2Furthermore, for the liquid crystal aligning agent (A-3) prepared by using a polyimide solution (PIS-3) in which the imidization rate was controlled in the process of chemically imidizing the polyamides containing DA-1 and DA-3, the afterimage characteristics were better in the range of 0.10 J / cm 2 The liquid crystal aligning agent (A-4) containing DA-1 and DA-4 can also obtain very good afterimage characteristics at very low exposure, similar to the liquid crystal aligning agent (A-3).
[0270] On the other hand, the liquid crystal aligning agent (A-5) containing DA-3 and DA-5 and DC-1 and DC-2 shown in Comparative Example 1 showed good image sticking characteristics, but required 0.20 J / cm 2 From the viewpoint of the required exposure, the required exposure when the above-mentioned liquid crystal aligning agents (A-2, A-3, A-4) show good afterimage characteristics is 0.10 J / cm 2 Furthermore, the required exposure amount can be adjusted by the combination of polymer units, so the takt time desired by the user can be achieved when considering the actual manufacturing site.
[0271] In addition, the liquid crystal alignment agent (A-6) obtained from DA-3, DA-5 and DC-1 has a mother skeleton similar to the above-mentioned liquid crystal alignment agents (A-1, A-2, A-3, A-4), but does not obtain good afterimage characteristics, thus suggesting the superiority of using DA-1 included in the present claims.
[0272] [Example 5]
[0273] The liquid crystal unit for image sticking evaluation prepared by using the liquid crystal alignment agent (A-1) in Example 1 was heated in a heating oven at 60°C for more than 2 weeks, and then observed with a polarizing microscope (ECLIPSE E600WPOL) (manufactured by NIKON CORPORATION). It should be noted that the judgment criteria are as described above, and the number of bright spots confirmed by polarizing microscope observation is recorded as "good" if the number is less than 5, and "bad" if the number is more than 5. The bright spot evaluation results of the liquid crystal unit after long-term AC drive are shown in Table 6.
[0274] [Examples 6, 7, 8]
[0275] Liquid crystal cells for poor display evaluation were prepared by using each liquid crystal aligning agent (A-2, A-3, A-4) instead of the liquid crystal aligning agent (A-1) and changing the ultraviolet irradiation amount and the calcination temperature to the same method as in Example 5. Each poor display evaluation result is shown in Table 6 below.
[0276] [Comparative Examples 3 and 4]
[0277] Liquid crystal cells for poor display evaluation were prepared by using each liquid crystal aligning agent (A-5, A-6) instead of the liquid crystal aligning agent (A-1) and changing the irradiation amount of ultraviolet rays and the calcination temperature to the same method as in Example 5. Each poor display evaluation result is shown in Table 6 below.
[0278] [Table 6]
[0279]
[0280] The liquid crystal alignment agents (A-1, A-2, A-3, A-4) containing DA-1 and DC-1 described in the present claims showed very good results in the evaluation of poor performance. On the other hand, the liquid crystal alignment agents containing the soluble polyimide obtained by copolymerizing DA-3 and DA-5 and DC-1 and DC-2 shown in Comparative Example 1 and the soluble polyimide obtained by copolymerizing DA-3, DA-5 and DC-1 showed no poor performance. The liquid crystal alignment agent containing the soluble polyimide using DA-1 contained in the present claims also has an effect on suppressing poor performance.
[0281] [Synthesis Example 23]
[0282] Polymerization of DC-3 / DA-6 polyamic acid
[0283] In a 50mL four-necked flask with a stirring device and a nitrogen inlet tube, 4.00g (8.50mmol) of DA-6 was taken, 40.58g of NMP was added, and the mixture was stirred and dissolved at room temperature for 10 minutes while nitrogen was sent. 1.54g (7.64mmol) of DC-3 was added to the diamine solution while stirring, and stirred for 24 hours at room temperature to obtain a solution of polyamic acid (PAA-8) with a concentration of 12% by mass. The viscosity of the polyamic acid solution at a temperature of 25°C was 420mPa·s. In addition, the molecular weight and molecular weight distribution of the polyamic acid were Mn=9.82×10 3 , Mw=2.16×10 4 , Mw / Mn=2.20.
[0284] [Synthesis Examples 24, 25, 26, 27, 28, 29]
[0285] The diamine components, tetracarboxylic acid components, and NMP shown in Table 7 below were used, and the reaction temperature and solid content concentration were carried out in the same manner as in Synthesis Example 1, thereby obtaining polyamic acid solutions PAA-9, PAA-10, PAA-11, PAA-12, PAA-13, and PAA-14 shown in Table 7 below. The viscosity and molecular weight of the obtained polyamic acid are shown in Table 8 below.
[0286] [Table 7]
[0287]
[0288] [Table 8]
[0289]
[0290] [Synthesis Example 30]
[0291] In a 100ml four-necked flask with a stirring device and a nitrogen inlet tube, 30.0g of the obtained polyamic acid solution (PAA-8, PAA-9, PAA-10, PAA-11, PAA-12, PAA-13, PAA-14) was taken respectively, 30.0g of NMP was added, and stirred at room temperature for 30 minutes. Acetic anhydride and 5mol times of pyridine were added to the obtained polyamic acid solution relative to the carboxylic acid of the polyamic acid, and heated and stirred for 3 hours at 70°C for chemical imidization. The obtained reaction solution was put into 500ml of methanol while stirring, and the precipitated precipitate was recovered, and then washed 3 times with 300ml of methanol. The obtained resin powder was dried at 80°C for 12 hours to obtain polyimide resin powder (PIP-8, PIP-9, PIP-10, PIP-11, PIP-12, PIP-13). Regarding PIP-14, gelation occurred during chemical imidization, and thus polyimide could not be obtained. The molecular weight and imidization ratio of the polyimide resin powder are shown in Table 9 below.
[0292] [Table 9]
[0293]
[0294] [Examples 7 to 12]
[0295] 10.0 g of the polyamic acid solution (PAA-8 to PAA-14) obtained above was weighed into a 50 ml eggplant flask, 4.00 g of NMP and 6.0 g of BCS were added, and stirred at room temperature for 24 hours to obtain liquid crystal aligning agents (A-8 to A-14). A-14 was used as a comparative object.
[0296] [Examples 13 to 18]
[0297] 2.0 g of the polyimide resin powder (PIP-8 to PIP-13) obtained above was weighed into a 50 ml eggplant flask, 18.0 g of NMP was added, and the mixture was stirred at room temperature for 24 hours. 6.67 g of NMP and 6.67 g of BCS were further added, and the mixture was stirred for 1 hour to obtain liquid crystal aligning agents (A-15 to A-20).
[0298] [Test Example 1]
[0299] The evaluation of the liquid crystal alignment film was carried out based on the following method about the alignment agent A-8 to A-20 obtained in Examples 7 to 18. Moreover, as a comparative object, A-14 (Comparative Example 3) and SE-6414 (Comparative Example 4) manufactured by Nissan Chemical Co., Ltd. were used.
[0300] <Evaluation of Liquid Crystal Orientation, Voltage Retention Ratio, and Pretilt Angle>
[0301] The liquid crystal orientation, voltage holding ratio, and pretilt angle were evaluated as follows.
[0302] [Preparation of a Liquid Crystal Cell for Observation of Liquid Crystal Orientation and Measurement of Voltage Retention Ratio and Pretilt Angle]
[0303] After filtering the liquid crystal alignment agent with a 1.0 μm filter, apply it on a substrate with an electrode (a glass substrate with a size of 30 mm horizontally × 40 mm vertically and a thickness of 0.7 mm. The electrode is a rectangular ITO electrode with a width of 10 mm × a length of 40 mm and a thickness of 35 nm) by spin coating. Prepare a substrate that has been dried on a hot plate at 80°C for 1 minute and then fired in an IR oven at 120°C for 20 minutes and a substrate that has been fired at 230°C. The film thickness becomes 100 nm after firing. The liquid crystal alignment film is brushed with rayon cloth (YA-20R made by Yoshikawa Chemical Industry) (roller diameter: 120 mm, roller rotation speed: 1000 rpm, moving speed: 20 mm / second, and pressing length: 0.4 mm), and then cleaned by ultrasonic irradiation in pure water for 1 minute. After removing water droplets by blowing, dry it at 80°C for 15 minutes to obtain a substrate with a liquid crystal alignment film.
[0304] Prepare two substrates with liquid crystal alignment films, spread 4 μm spacers on the surface of one of the liquid crystal alignment films, print a sealant thereon, and bond the other substrate in the opposite direction of the brushing direction and with the film surfaces facing each other, and then cure the sealant to make an empty cell. MLC-3019 (Merck) was injected into the empty cell by a reduced pressure injection method, and the injection port was sealed to obtain a liquid crystal cell. After that, after observing the orientation of the liquid crystal, the liquid crystal cell was heated at 110°C for 1 hour and left at 23°C overnight to obtain a liquid crystal cell for voltage holding ratio measurement.
[0305] Using the voltage holding ratio measurement liquid crystal cell obtained by the above steps, a voltage of 1 V was applied for 60 μs at a temperature of 60° C., and the voltage after 166.7 ms was measured, and the voltage that could be maintained was calculated as the voltage holding ratio. It should be noted that the voltage holding ratio was measured using a VHR-1 voltage holding ratio measurement device manufactured by TOYO Corporation.
[0306] [Evaluation of pretilt angle]
[0307] The pretilt angle was measured using an AxoScan Mueller matrix polarimeter manufactured by Optometrics Corporation.
[0308] [Evaluation of brush abrasion resistance]
[0309] After filtering the liquid crystal alignment agent with a 1.0 μm filter, apply it on a substrate with an electrode (a glass substrate with a size of 30 mm horizontally × 40 mm vertically and a thickness of 1.1 mm. The electrode is a rectangular ITO electrode with a width of 10 mm × a length of 40 mm and a thickness of 35 nm) by spin coating. Prepare a substrate that has been dried on a hot plate at 80°C for 1 minute and then fired in an IR oven at 120°C for 20 minutes and a substrate that has been fired at 230°C. The film thickness becomes 100 nm after firing. The liquid crystal alignment film is brushed with a rayon cloth (YA-20R manufactured by Yoshikawa Chemical Industry) (roller diameter: 120 mm, roller speed: 1000 rpm, moving speed: 20 mm / second, and pressing length: 0.5 mm), and then the brushing resistance is evaluated using a confocal laser microscope. In the case of peeling, it is recorded as peeling, in the case of seeing a lot of debris and scratches, it is recorded as bad, and in the case of good, it is recorded as good.
[0310] [Evaluation of Liquid Crystal Orientation]
[0311] The liquid crystal orientation was evaluated based on the same evaluation criteria as in Example 1. In addition, “0” in the above evaluation criteria was recorded as “good”, and “×” in the above evaluation criteria was recorded as “bad”.
[0312] The results of the above-mentioned various evaluations are shown in Tables 10 to 13.
[0313] <Evaluation results of printability, brush resistance, and unit display properties of the alignment agent>
[0314] [Table 10]
[0315] 120℃ firing
[0316] Example Liquid crystal alignment agent Material Brush resistance Liquid crystal orientation 7 A-8 PAA-8 good good 8 A-9 PAA-9 good good 9 A-10 PAA-10 good good 10 A-11 PAA-11 good good 11 A-12 PAA-12 good good 12 A-13 PAA-13 good good 13 A-15 PIP-8 good good 14 A-16 PIP-9 good good 15 A-17 PIP-10 good good 16 A-18 PIP-11 good good 17 A-19 PIP-12 good good 18 A-20 PIP-13 good good Comparative Example 3 A-14 PAA-14 bad bad Comparative Example 4 SE-6414 - bad bad
[0317] [Table 11]
[0318] 120℃ firing
[0319]
[0320] [Table 12]
[0321] 230℃ firing
[0322] Example Liquid crystal alignment agent Material Brush resistance Liquid crystal orientation 7 A-8 PAA-8 good good 8 A-9 PAA-9 good good 9 A-10 PAA-10 good good 10 A-11 PAA-11 good good 11 A-12 PAA-12 good good 12 A-13 PAA-13 good good 13 A-15 PIP-8 good good 14 A-16 PIP-9 good good 15 A-17 PIP-10 good good 16 A-18 PIP-11 good good 17 A-19 PIP-12 good good 18 A-20 PIP-13 good good Comparative Example 3 A-14 PAA-14 bad good Comparative Example 4 SE-6414 - good good
[0323] [Table 13]
[0324] 230℃ firing
[0325]
[0326] When the film is formed by calcining at 120°C, polyamic acid in particular cannot be imidized under this condition, so the physical strength becomes very weak, the film is scraped by the brushing treatment, and the orientation of the liquid crystal is also deteriorated. However, the polyamic acid and polyimide using the diamine of the present invention have very excellent brushing resistance and good liquid crystal orientation even under low-temperature calcination. Furthermore, the pretilt angle is also very small and the VHR is also high.
[0327] Furthermore, the diamine of the present invention can make the solubility very high. PAA-14 that is not introduced cannot be chemically imidized, but when 50 mol% of PIP-13 is introduced as a diamine component, the imidization rate can be adjusted to 95% or more without any problem, and good alignment film characteristics are obtained. Generally, when components with very poor solubility such as DC-1 and DC-4 are incorporated, chemical imidization is often difficult, but by using the diamine of the present invention, a soluble polyimide with a high imidization rate can be adjusted. By making a soluble polyimide, reliability can also be improved.
[0328] When fired at 230°C, the material of the comparative example also undergoes imidization, so the brush abrasion resistance, liquid crystal orientation, and reliability are improved, but the orientation agent of the present invention shows good characteristics, and the pretilt angle tends to increase slightly, which is a very small advantage compared to the comparative object. Furthermore, the reliability becomes very high.
[0329] Therefore, by using the diamine of the present invention, a liquid crystal aligning agent that can be used for firing at any temperature from low temperature to high temperature can be produced, and an aligning film having a very low pretilt can be obtained.
[0330] [Test Example 2]
[0331] The liquid crystal alignment agents (A-16, A-17, A-20) obtained in Example 14, Example 15, and Example 18 and the liquid crystal alignment agent A-5 of the comparative example were filtered through a 1.0 μm filter, and then the liquid crystal alignment agents were applied on a 30 mm × 40 mm ITO substrate by spin coating, and dried on a hot plate at 80° C. for 2 minutes. The coating surface was subjected to a light irradiation at 0.1 to 1.0 J / cm 2 through a polarizing plate. 2 After irradiating the ultraviolet rays with a wavelength of 254nm and linear polarization with an extinction ratio of 26:1 in a range, the substrate was fired in a hot air circulation oven at 150°C for 20 minutes to obtain a substrate with a liquid crystal orientation film. The above-mentioned two substrates obtained are set as a group, and a sealant is printed on the substrate. After the other substrate is attached in a manner that the liquid crystal orientation film faces each other and the orientation direction becomes 0°, the sealant is cured to produce an empty unit. Liquid crystal MLC-3019 (manufactured by Merck) is injected into the empty unit by a reduced pressure injection method, and the injection port is sealed to obtain a liquid crystal orientation liquid crystal unit. The results of each liquid crystal orientation are shown in the following Table 14. It should be noted that the evaluation is based on the same evaluation criteria as in Example 1.
[0332] [Table 14]
[0333]
[0334] It is known that the soluble polyimide using the diamine of the present invention and DC-1 exhibits orientation when irradiated with UV after temporary drying and fired at 150°C. The material of Comparative Example 1 exhibits orientation at high temperatures, but does not exhibit orientation at low temperatures regardless of the intensity of UV irradiation. Therefore, it is known that photo-orientation at low temperatures can be achieved by using the diamine of the present invention.
[0335] Industrial Applicability
[0336] The polyamic acid and polyimide obtained from the diamine of the present invention have excellent solubility in solvents, thus making it possible to manufacture liquid crystal alignment agents and films that have been impossible to achieve from the perspective of solubility. In addition, it can be widely used in everything from alignment films for brushing to photo-alignment films. In particular, it is believed that it can cope with low-temperature sintering, low pretilt angle materials, and simplified photo-alignment processes that are the trend of future lateral electric field methods.
[0337] The liquid crystal display element having the liquid crystal alignment film made of the material of the present invention has excellent afterimage characteristics and long-term display stabilization, and can be suitably used in large-screen and high-definition liquid crystal televisions, small and medium-sized car navigation systems, smart phones, etc. Furthermore, it can be made more simply in the manufacturing process, so it can be expected that the yield and production efficiency can be improved.
Claims
1. A liquid crystal aligning agent comprising at least one polymer selected from a polyimide precursor containing a structural unit represented by the following formula [3-1] and a polyimide as an imide compound thereof, In formula [3-1], V 0 is a tetravalent organic group derived from a tetracarboxylic acid derivative, W 1 is a divalent organic group represented by the following formula [2-1], R 3 and R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, In formula [2-1], Y 1 is a tetravalent organic group having an alicyclic structure, X 1 , X 2 is a divalent organic group, Z 1 , Z 2 are each independently a single bond, -NH-, or -O-, R 1 and R 2 Each independently represents an alkyl group having 1 to 5 carbon atoms, and * represents a bonding site.
2. The liquid crystal alignment agent according to claim 1, wherein X of the formula [2-1] 1 , X 2 It is a divalent organic group having a phenylene group.
3. The liquid crystal aligning agent according to claim 1 or 2, wherein: X of the formula [2-1] 1 , X 2 is a divalent organic group represented by the following formula [2-2], In formula [2-2], X 3 , X 5 independently represent a phenylene group which may have a substituent; 4 represents a divalent group having 10 or less carbon atoms; L 1 , L 2 independently represent a single bond, -O-, or -S-; n1 and n2 independently represent 0 or 1; *1 and *2 represent a bonding site, and one of *1 and *2 is identical to Z 1 or Z 2 bonded to one atom and the other bonded to a nitrogen atom.
4. The liquid crystal aligning agent according to claim 1 or 2, wherein In the formula [2-1], the tetravalent organic group having an alicyclic structure is selected from the following formula [Y 1 -1]~Formula[Y 1 -20], Formula [Y 1 -1]~Formula[Y 1 -4], R 5 ~R 25 Each is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, or a phenyl group, and they may be the same or different. 5 . A liquid crystal alignment film obtained from the liquid crystal aligning agent according to claim 1 . 6 . A liquid crystal display element comprising the liquid crystal aligning film according to claim 5 .
7. A diamine represented by the following formula [1], In formula [1], Y 1 is a tetravalent organic group having an alicyclic structure, X 1 , X 2 is a divalent organic group, Z 1 , Z 2 are each independently a single bond, -NH-, or -O-, R 1 and R 2 each independently represents an alkyl group having 1 to 5 carbon atoms, The tetravalent organic group having an alicyclic structure is selected from the following formula [Y 1 -1]~Formula[Y 1 -20], Formula [Y 1 -1]~Formula[Y 1 -4], R 5 ~R 25 Each is independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, or a phenyl group, and they may be the same or different. 8 . A polymer obtained from a diamine component comprising the diamine according to claim 7 .
9. A method for producing a diamine compound, wherein: The diamine according to claim 7 is produced by using a compound of the following formula (11) as a starting material via a compound of the following formula (12) or a compound of the following formula (13), In formulas (11) to (13), Y 1 is a tetravalent organic group having an alicyclic structure as defined in claim 7, R 1 and R 2 Each independently represents an alkyl group having 1 to 5 carbon atoms, and in formula (13), R 31 and R 32 It represents a protecting group for a hydrogen atom or an amino group.
